Respon Intensitas Cahaya Terhadap Daya Tetas Telur dan Perkembangan Larva Ikan Patin Siam (Pangasianodon Hypopthalmus. F) - Ishak Maulidin; Muhammad Sugihartono; Muarofah Ghofur (Jurnal Akuakultur Sungai dan Danau, 2023)
This study aims to see the effect of light intensity on the hatchability of catfish (P. hypopthalmus. F) eggs. This research was conducted in December 2021, for 30 days at the Inti Karya Perdana Sijenjang Farmers Group, Jambi province. The design in this study was a completely randomized design (CRD) with 4 levels and 3 replications, the treatments included: without light (A), 20 watt light (B), 30 watt light (C) and 40 watt light (D). Parameters observed included egg hatchability, hatching time, survival rate and water quality. The results showed that the average hatchability of eggs was 83.00 ± 5.46 % and ranged from 78.00 ± 2.65 to 90.67 ± 2.08 %. The average value of hatching time was 19.71 ± 2.31 hours, minutes. The average survival rate was 85.75 ± 4.03% and ranged from 80.67 ± 3.51 to 90.00 ± 3.61%. The temperature of the media for hatching catfish eggs ranged from 26.82-30.500C in the morning and 29.50-31.830C in the afternoon, the pH ranged from 6.65-7.76 in the morning and 6.23-6.78 in the afternoon. afternoon. Dissolved oxygen ranged from 4.3-4.5 mg/L, CO2 ranged from 13-15 mg/L and ammonia for all treatments was 0.001 mg/L. The temperature of the larval rearing medium during the study ranged from 26.93ºC-31.11 ºC in the morning and 27.47ºC-31.45ºC in the afternoon, the pH ranged from 6.32-7.34 in the morning and 6.10-7. .81 in the afternoon, dissolved oxygen ranged from 4.0-4.3 mg/L, CO2 ranged from 12-13 mg/L and ammonia was 0.001 mg/L. Differences in light intensity in the form of different lamp watts affect egg hatchability and hatching time for Siamese catfish (P. hypopthalmus. F.) eggs.